A possible role of GDNF expression by which cabergoline use affects corpus callosum - Georgios Mitsiakos; Anastasia Gkampeta (Hygeia Press di Corridori Marinella, 2018)
A variety of malformations have been associated with cabergoline use during gestation. Recently we had a preterm male infant referred to our Neonatal Intensive Care Unit diagnosed with corpus callosum agenesis confirmed by brain ultrasound and brain magnetic resonance imaging. The mother was on medication with cabergoline, due to a pituitary prolactinoma, only for the first month of pregnancy. The exact possible mechanism by witch cabergoline may have a negative effect on corpus callosum development is still unknown. Discovery of neurotrophic brain factors has opened a new chapter in the understanding of neurogenesis and synaptic plasticity mechanisms. To our knowledge, this is the first suggestion of a possible role of glial cell line-derived neurotrophic factor (GDNF) expression on corpus callosum agenesis after the administration of cabergoline in women during pregnancy.